A Comparative Life Cycle Assessment (LCA) of Warm Mix Asphalt (WMA) and Hot Mix Asphalt (HMA) Pavement: A Case Study in China - Hui Ma; Zhigang Zhang; Xia Zhao; Shuang Wu (Advances in Civil Engineering)
Generally, the warm mix asphalt (WMA) technology can reduce the mixing and paving temperature effectively as compared with that of hot mix asphalt (HMA), which is considered more environment-friendly. In this study, the environmental impacts and resource consumptions of WMA and HMA pavements were analyzed comparatively using the life cycle assessment (LCA) method. A LCA model of pavement was built; meanwhile, the relevant life cycle inventory (LCI) of WMA and HMA pavements was also collected and analyzed. The midpoint impact categories including Global Warming Potential (GWP), Chinese Abiotic Depletion Potential (CADP), and Particulate Matter Formation (PMF) were assessed for five cases. The assessment results showed that the resource consumptions of both WMA and HMA pavements in entire life were almost at the same level, while the environmental impacts of WMA pavement related to greenhouse gases and PM2.5 emissions were significantly less than that of HMA pavement, except for the case where the long-term performance of WMA pavement is much worse than that of HMA pavement. In final, it could be concluded that WMA pavement is more environment-friendly compared with HMA pavement although they have the same-level resource consumptions.